Mining Dispute National Strike (page 24)
1926-06-25 "Mining Dispute National Strike (page 24)" [g0494024.jpg], 25 June 1926, Trades Union Congress Report of the General Council to the Conference of Executives of Affiliated Unions, 25th June 1926.